Aged-based differences in spatial language skills from 6 to 10 years: Relations with spatial and mathematics skills. (June 2021) - Gilligan-Lee, Katie A.; Hodgkiss, Alex; Thomas, Michael S.C.; Patel, Pari K.; Farran, Emily K.
Abstract: Spatial language is the language of spatial concepts and spatial relationships. Prior research has demonstrated an association between spatial language and spatial thinking in pre-school children. However, there is limited evidence exploring age-based differences in spatial language in older childhood. This cross-sectional study has three main aims. First, we present a novel spatial language measure and show differences in spatial language performance across age groups from 6 to 10 years (N = 155). Second, having demonstrated that our measure is sensitive to age-based progression, we use regression analyses to determine relations between spatial language and performance on a range of spatial tasks ( r 2 :1.2%–9.0%). Third, we investigate the relations between spatial language and different mathematics skills ( r 2 :0.2%–15.4%) and propose mechanisms that may explain these associations. We discuss how these findings lay a foundation for future spatial language interventions as a novel tool which may lead to educational improvements in mathematics. Highlights: Spatial language skills show progression between 6 and 10 years. Spatial language comprehension is stronger than production in middle childhood. Spatial language is associated with performance on some spatial measures. Spatial language is a significant predictor of a range of mathematics skills. These findings lay a foundation for future spatial language interventions.